Learning System Resilience in the Face of Demographic Shifts: Adaptive Response Design and Institutional Collaboration - Panecekak, Suhaimi (EDUCARE: Jurnal Ilmu Pendidikan, 2025)
This study aims to analyze the resilience of learning systems in responding to demographic changes through adaptive strategies and institutional collaboration. Using a descriptive qualitative approach, data were collected through in-depth interviews, participant observation, and documentation at several educational institutions facing the dynamics of cross-age student populations. The results of the study indicate that system resilience is built through curriculum reorientation, cross-generational teacher training, and flexible and technology-based learning management. These adaptive strategies are strengthened by collaborative practices between educational institutions, government, and communities that are systematically documented. These findings highlight the importance of institutional innovation that is responsive to social dynamics in achieving inclusive and sustainable education. This study recommends developing a collaborative model as a foundation for designing a future learning system that is resilient to demographic pressures.